Rhamnidium riograndense (Rhamnaceae), a new species from southern Brazil - Figueira, Maurício; Schindler, Bianca (Phytotaxa, 2021)
A new species, Rhamnidium riograndense, from southern Brazil, is here described and illustrated. We present information about its distribution, habitat, phenology, conservation status and a key for all the South American species of the genus is provided. The new species is endemic to the central part of the state of Rio Grande do Sul, in the transition between Paraná and Pampean provinces in rocky habitats, mostly mountain slopes, where only four populations are currently known.